2007
DOI: 10.1016/j.clindermatol.2007.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Gene-environment interactions in sarcoidosis: challenge and opportunity

Abstract: Susceptibility to most human diseases is polygenic, with complex interactions between functional polymorphisms of single genes governing disease incidence, phenotype, or both. In this context, the contribution of any discrete gene is generally modest for a single individual, but may confer substantial attributable risk on a population level. Environmental exposure can modify the effects of a polymorphism, either by providing a necessary substrate for development of human disease or because the effects of a giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 56 publications
0
29
0
1
Order By: Relevance
“…Genetic factors can be important in deWning the pattern of disease presentation, its severity and prognosis. Several investigators have searched for associations with human leucocyte antigen (HLA)-related genes that may confer susceptibility to sarcoidosis, suggesting that haplotype HLA-DRB1*1101 can predispose people to development of this disease [18][19][20].…”
Section: Aetiopathogenesismentioning
confidence: 99%
“…Genetic factors can be important in deWning the pattern of disease presentation, its severity and prognosis. Several investigators have searched for associations with human leucocyte antigen (HLA)-related genes that may confer susceptibility to sarcoidosis, suggesting that haplotype HLA-DRB1*1101 can predispose people to development of this disease [18][19][20].…”
Section: Aetiopathogenesismentioning
confidence: 99%
“…Silica granulomatosis is a delayed hypersensitivity response to crystalline silica. The biological plausibility of a relationship between exposure to silica and autoimmune and inflammatory disorders has already been proposed [1][2][3]. Recently, SOL脌 et al [6] reported a very interesting case suggesting a new association between ingestion of anhydrous colloidal silica (a vehicle for some oral drug formulations) and sarcoidosis.…”
Section: To the Editorsmentioning
confidence: 99%
“…Many causative agents are considered to be involved in the pathogenesis [1][2][3][4][5]. Geneenvironment interactions offer the potential for strengthening the evidence of causation between exposures and sarcoidosis.…”
Section: To the Editorsmentioning
confidence: 99%
See 1 more Smart Citation
“…To that end, models that are capable of investigating multiple biologic processes simultaneously are more likely to provide insights into human disease pathogenesis. Such a "multiple hit" hypothesis has been forwarded for many ILDs, such as hypersensitivity pneumonitis (12), sarcoidosis (13), and IPF (14). Determining whether this hypothesis is true will require models that take multiple genetic, environmental, and host immunological aberrations into account.…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%